GENERALIZED NONLOCAL BOUNDARY CONDITION FOR FRACTIONAL PANTOGRAPH DIFFERENTIAL EQUATION VIA HILFER FRACTIONAL DERIVATIVE - Ahmed, I.; Kumam, P.; Tariboon, J.; Ibrahim, A.; Borisut, P.; Demba, M. A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2021)
Fractional calculus has been very popular due to the application in real world problems. This paper aimed to investigate the existence, uniqueness and Ulam stability for nonlinear fractional pantograph differential equations with generalized nonlocal boundary conditions involving Hilfer fractional derivative. The analysis were done through Banach and Kranoselskii’s fixed point theorems. Finally, example are given to illustrate the theoretical results.